Pengaruh Penggunaan Aplikasi Google Classroom Terhadap Hasil Belajar Siswa Kelas X TKJ SMKN 3 Padangsidimpuan Sumatra Utara - Ardhi, Muhammad Riesyaf; Sesmiarni, Zulfani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was motivated by the problems that the researchers found, such as the use of Googleclassroom application learning technology in schools. Its use is still early in schools so students and teachers still have to continue to learn how to use it. Based on this background, the purpose of this study is to find out how much influence the use of the Google classroom application has on student learning outcomes. This research was conducted at SMKN 3 Padangsidimpuan. Experimental research method is a quantitative research method used in this study. The design in this study used a pretest posttest control group design. North Sumatra, The results of the research on the effect of the use of the google classroom application on student learning outcomes indicate that there is an influence on the use of the google classroom application on student learning outcomes in computer and basic networking subjects. This is evidenced by the sampling carried out using purposive sampling technique, namely the first sample amounted to 36 students in the experimental class using the google classroomapplication and the second sample amounted to 36 students in the control class using conventionallearning media. The average posttest score for the experimental class was 79.13 and the control classwas 73.21. The results of the hypothesis using the t-test at a significant level of 0.05 obtained sig (2-tailed) of 0.002. So H0 is rejected and H1 is accepted because 0.002 <0.05. This shows that there is an effect of using the google classroom application on student learning outcomes in basic computer and network subjects.